Studi Literature Solusi Keuangan Islam Mencegah Krisis Masa Depan - Rijal Allamah Harahap; Herwan Nafil; M.Shabri Abd.Majid; Marliyah Marliyah; Rita Handayani (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The financial crisis is a problem that continues to occur, but the right solution has not been agreed upon to prevent it. Interest-based debt and its derivation is believed to be one of the causes of the emergence of the crisis. Interest-based financing causes the cost of obtaining capital to be higher. This triggers a bubble in the economy, where there is a gap between the real sector and the financial sector. This study offers a preventive solution to this crisis problem through a literature study approach. The findings of this study are that there is data that shows the Islamic financial system with its characteristics is able to withstand the crisis. In addition, the Islamic financial system based on profit sharing and risk balances the economy and is believed to be able to prevent a crisis from occurring. Keywords: Islamic Finance, Crisis, Solution